2018
DOI: 10.1038/s41398-017-0088-0
|View full text |Cite
|
Sign up to set email alerts
|

Whole-exome sequencing and gene-based rare variant association tests suggest that PLA2G4E might be a risk gene for panic disorder

Abstract: Panic disorder (PD) is characterized by recurrent and unexpected panic attacks, subsequent anticipatory anxiety, and phobic avoidance. Recent epidemiological and genetic studies have revealed that genetic factors contribute to the pathogenesis of PD. We performed whole-exome sequencing on one Japanese family, including multiple patients with panic disorder, which identified seven rare protein-altering variants. We then screened these genes in a Japanese PD case–control group (384 sporadic PD patients and 571 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…It was known to regulate synapse formation, synapse elimination (Ou et al, 2010;Park et al, 2011), hippocampal neurons related pathways, and hippocampal long-term potentiation (Cho et al, 2015;Joe et al, 2017). PLA2G4E was reported to be strongly expressed in the brain, especially in neurons (Ogura et al, 2016), and was associated with neurobehavioral disorders (Everson et al, 2019;Morimoto et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It was known to regulate synapse formation, synapse elimination (Ou et al, 2010;Park et al, 2011), hippocampal neurons related pathways, and hippocampal long-term potentiation (Cho et al, 2015;Joe et al, 2017). PLA2G4E was reported to be strongly expressed in the brain, especially in neurons (Ogura et al, 2016), and was associated with neurobehavioral disorders (Everson et al, 2019;Morimoto et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It is considered to be related to neural structure and function, a neurobehavioral disorder in research [60]. Some literature suggests that this gene may be a risk gene for panic disorder [61], there is also some literature indicating that there is a certain relationship between the occurrence of depression [62]. Cytosolic phospholipase A2 is closely related to axonal proliferation and excitotoxic damage under pathological conditions [63].…”
Section: Discussionmentioning
confidence: 99%
“…This gene encodes for a calcium-dependent N-acyltransferase; experimental mouse models have implicated that it likely plays a critical role in endocannabinoid signaling in the nervous system 58 and thus differential regulation of this gene has implications for neurodevelopment and neurodegenerative disorders 59 . In human observational studies, placental CpGs within PLA2G4E have been observed to be differentially methylated in association with extremely preterm births 60 and genetic variants within the PLA2G4E gene have been implicated as a potential risk factor for neurodevelopmental problems such as panic disorder 61 . The protein encoded by GRIK3 is involved in presynaptic neurotransmission, and has been associated with developmental delay 62 , schizophrenia 63 , obsessive-compulsive disorder 64 , and depression 65 .…”
Section: Discussionmentioning
confidence: 99%